The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3174/ajnr.a4363
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Predictive Value of a User-Independent Platform for CT Perfusion Analysis: Threshold-Derived Automated Systems Outperform Examiner-Driven Approaches in Outcome Prediction of Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE:Treatment strategies in acute ischemic stroke aim to curtail ischemic progression. Emerging paradigms propose patient subselection using imaging biomarkers derived from CT, CTA, and CT perfusion. We evaluated the performance of a fully-automated computational tool, hypothesizing enhancements compared with qualitative approaches. The correlation between imaging variables and clinical outcomes in a cohort of patients with acute ischemic stroke is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 25 publications
(53 reference statements)
0
68
0
Order By: Relevance
“…10 Briefly, 62 continuous patients (36 women; median age, 70 years; range, 33-94 years) with AIS (Ͻ12 hours) and MCA or intracranial ICA occlusion were identified from a prospectively collected, single-institution stroke registry and radiologic informatics query of 815 patients with ischemic stroke, spanning February 1, 2011, to December 31, 2013, with Emory University Hospital review board approval. All patients were evaluated initially by a dedicated vascular neurologist in the emergency setting, with initiation of institutional stroke protocol facilitating expedited triage, imaging, interpretation, and treatment when appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Briefly, 62 continuous patients (36 women; median age, 70 years; range, 33-94 years) with AIS (Ͻ12 hours) and MCA or intracranial ICA occlusion were identified from a prospectively collected, single-institution stroke registry and radiologic informatics query of 815 patients with ischemic stroke, spanning February 1, 2011, to December 31, 2013, with Emory University Hospital review board approval. All patients were evaluated initially by a dedicated vascular neurologist in the emergency setting, with initiation of institutional stroke protocol facilitating expedited triage, imaging, interpretation, and treatment when appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…9 We recently reported the benefits of a high-speed computing tool for CT perfusion analysis over qualitative approaches to imaging triage for prognostication among patients with anterior circulation AIS. 10 The findings therein suggested that a user-and vendor-independent computational tool may outperform purely qualitative approaches in outcome prediction. Similar implementations of this tool in recent, prospective endovascular trials suggested strong results as an approach to patient selection; however, the relative contribution of CTP-based selection criteria, among other trial-specific features, remains uncertain in light of the overall favorable outcomes reported across disparate trial designs.…”
mentioning
confidence: 99%
See 3 more Smart Citations